CILIP News - Health Promotion Librarian, a winner in national award - Thomas, Sue (Journal of EAHIL, 2017)
The Chartered Institute of Library and Information Professionals (CILIP) Wales is the leading professional body for librarians, information specialists and knowledge managers. The winners were announced at the CILIP Wales Annual Conference on 15 May 2014 in Cardiff. Sue Thomas, Librarian at the Health Promotion Library has won best librarian in the Public Sector category at the recent Chartered Institute of Library and Informational Professionals Wales annual awards. Sue was recognised for her work in bringing health information to the forefront and working in partnership with colleagues in public libraries to shape the health offer across Wales. The judges also recognised her involvement in the Book Prescription Wales Scheme, the Macmillan Library Projects and the Society of Chief Libraries Sub-Group on Health and Wellbeing.